Analisis Peran Kewirausahaan Islami Pada Usaha Mahasiswa Dalam Mendorong Kemandirian Dan Kesejahteraan Ekonomi - Shanda Sandriani; Fazila Sidik; Yulia Novita (CV Muara Edukasi, 2025)
In recent years, scholarly interest in Islamic entrepreneurship within the context of university students has grown substantially, particularly in relation to its potential to integrate spiritual values with economic development. This literature-based study examines existing research to identify how Islamic entrepreneurial principles contribute to students’ economic independence and overall economic well-being. By reviewing journal articles, books, and prior empirical studies, this paper synthesizes findings on the role of core Islamic values such as honesty, fairness, social responsibility, and trustworthiness in shaping entrepreneurial motivation, managerial competence, and innovative behavior among students. The reviewed literature consistently indicates that the application of Islamic ethical principles supports the development of sustainable income, enhances students’ socio-economic capabilities, and contributes to the broader formation of a moral economy rooted in Islamic teachings. Overall, the analysis highlights that Islamic entrepreneurship provides a holistic framework for student empowerment and has significant implications for fostering ethical and independent young entrepreneurs